Kompetensi Peradilan Agama Menangani Perkara Cerai Gugat dalam Tinjauan Fikih Islam - A. Zamakhsyari Baharuddin; Rifqi Qowiyul Iman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
This study aims to highlight the review of Islamic jurisprudence regarding the competence of religious courts in handling judicial divorce as a reflection of the view that judges' actions to terminate the marriage relationship are unjustifiable and the only divorce institution is divorce which is husband's prerogative. The method applied is descriptive-analytic research method with the main data source is library research. The results of this study indicate that the Religious Court is not only a state institution, but also a religious institution as recorded in the Islamic literature, and a judge with the authority to pronounce divorce is actually playing the role of amar makruf nahi mungkar, therefor his authority is not only legally valid in the state law, but also has its own legitimacy regulated in Islamic jurisprudence.